Routine nasal surgery: an audit of outpatient follow-up. Issue 843 (January 1996) - Murthy, P.; McKerrow, W. S.
Abstract : The study objective was to assess the value of outpatient follow-up of patients who undergo routine uncomplicated nasal surgery. A total of 177 postoperative patients (117 males, 60 females) undergoing routine nasal surgery at the Raigmore Hospital, Inverness, was selected over a six-month period, 92 of whom (60 males, 32 females) were requested to return to the clinic for a follow-up session. A total of 72 (78.3%) patients attended for post-operative review. Of these, 55 patients (76.4%) had achieved a satisfactory result from surgery and 17 (23.6%) required additional treatment for persistent problems. The former group were pleased with the outcome of their operation and required no further treatment. Of the 25 patients who were prescribed medication at the time of discharge from hospital, 19 (76.0%) were still complying with the medication and required no further specialist assistance. The results suggest that routine follow-up of uncomplicated cases of nasal surgery is unnecessary. The good therapeutic results in the majority of cases indicate a need to decrease the number of routine reviews to reduce the high non-attendance rate and increase the proportion of new patients seen at outpatient clinics. The role played by general practitioners is vital to this cause. This would include minor postoperative care, monitoring of prescribed medication and review of patients with occasional postoperative problems.